A low-velocity water-meter - Hutchings, Charles Ross (My University, 1894)
Introduction: The demand for a water-meter to measure accurately very low velocities of flow has not as yet been met satisfactorily. The occasion for measuring the flow in the hot-water healing system used in the college green houses, was the cause for my study of this subject and the construction of such an instrument has been made the subject of this production. It is known that the velocities within such a system are very low but how low is not known. This is desirable for the sanitary engineer in designing a plant of this kind. It is desirable too, for testing the efficiency of a place and measuring accurately the amount of heat carried by its circulation, that all variations and velocities be measured with accuracy. The meter, then, to answer these requirements must respond readily to any variation in flow, must be sensitive enough to indicate all appreciable flows and must not offer any considerable resistance or obstruction to the movement of the water.
Citation: Hutchings, Charles Ross. A low-velocity water-meter. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Velocity; Water meter; Voltage; Invention; Science; Machine; Theses; Manuscripts (documents)